Rapid onset and progression of myelopathy following an STI: a case for screening?. (1st March 2019) - Caswell, Rachel J; Nall, Peter; Boothby, Meg; Taylor, Graham P
Abstract : Human T lymphotropic virus type 1 (HTLV-1) is recognised as an STI with serious manifestations of the disease in approximately 10% of those infected. This case report is the first to describe the short interval from sexual acquisition of HTLV-1 to the onset of HTLV-1-associated myelopathy and rapid progression to spastic paraparesis. The number of adult infections in the UK per annum is unknown, but surveillance data indicate that around 30% of newly diagnosed infections are occurring in persons born in the UK, rather than in migrants from HTLV-1-endemic regions. Despite this, and despite the risk of chronic debilitating disease, HTLV-1 infection is not part of sexual health screening in the UK, with the consequence that patients requesting sexual health screens are not informed of their carrier status and transmission from asymptomatic carriers to the partners will continue.